Sea Reclamation in Mainland China: Process, Pattern, and Management. (April 2023) - Yan, Fengqin; Wang, Xuege; Huang, Chong; Zhang, Junjue; Su, Fenzhen; Zhao, Yifei; Lyne, Vincent
Abstract: Since the 1980 s, human activities and climate change have changed China's coastal zone rapidly and extensively. Sustainable management policies and regulations need to be based on an understanding of how all these drivers have shaped China's maritime estate, and what/where the future management priorities are. Using multisource remote sensing (RS) data, we investigated sea reclamation and coastline changes over the past four decades in development hotspots, provinces, and coastal environment types along China's coastline. China's artificial coastlines increased from 24% to 70.9% in four decades. Sea reclamation was mostly dominated by aquaculture ponds, ports, and agricultural land. The total coastal reclamation intensity (CRI) increased, as did coastline pressure, by 39.7% from 1980 to 2018. Since 2000, artificial coastlines have grown longer than, and at the expense of, natural coastlines. Population growth, economic development, and government policies were key drivers of past changes. Our characterization provides baseline information on drivers, structure and trends at hotspots, provinces, and environment types for future coastal management in China. We recommend future changes be monitored with a three-dimensional coastal zone observation network to assist real-time monitoring, enforcement and sustainable management of all coastal zone activities and coastline changes. Highlights: The percentage of artificial coastlines increased from 24% to 70.9% over the last four decades. Sea reclamation has mostly focused on the construction of aquaculture ponds, ports and agricultural land since 1980 in mainland China. Coastline pressure increased from 255.4 in 1980–356.9 person/km in 2018, increasing by 39.7%. Population growth, economic development, and government policies all played an important role in sea reclamation. Some suggestions for future coastal management and protection in China were provided.